2019
DOI: 10.1002/hep.30790
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Complex 1 Signaling Is Required for the Dedifferentiation From Biliary Cell to Bipotential Progenitor Cell in Zebrafish Liver Regeneration

Abstract: The liver has a high regenerative capacity. Upon two‐thirds partial hepatectomy, the hepatocytes proliferate and contribute to liver regeneration. After severe liver injury, when the proliferation of residual hepatocytes is blocked, the biliary epithelial cells (BECs) lose their morphology and express hepatoblast and endoderm markers, dedifferentiate into bipotential progenitor cells (BP‐PCs), then proliferate and redifferentiate into mature hepatocytes. Little is known about the mechanisms involved in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 54 publications
(86 reference statements)
1
66
2
Order By: Relevance
“…In addition, mTORC1 and the BMP pathway were found to regulate the conversion of biliary epithelial cells to hepatocytes in zebrafish [55,56]. Inhibition of the mTORC1 signaling pathway abolished the conversion from biliary epithelial cells to hepatoblast-like cells via decreased Urb2-mediated protein synthesis [56], whereas the BMP pathway controlled the conversion of biliary epithelial cells through Tbx2b expression [55]. These studies together show several important signaling and epigenetic factors underlying biliary epithelial cell plasticity in zebrafish.…”
Section: Mechanism Of Biliary Epithelial Cell Plasticitymentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, mTORC1 and the BMP pathway were found to regulate the conversion of biliary epithelial cells to hepatocytes in zebrafish [55,56]. Inhibition of the mTORC1 signaling pathway abolished the conversion from biliary epithelial cells to hepatoblast-like cells via decreased Urb2-mediated protein synthesis [56], whereas the BMP pathway controlled the conversion of biliary epithelial cells through Tbx2b expression [55]. These studies together show several important signaling and epigenetic factors underlying biliary epithelial cell plasticity in zebrafish.…”
Section: Mechanism Of Biliary Epithelial Cell Plasticitymentioning
confidence: 84%
“…Inhibition of the bromodomain and extraterminal (BET) protein blocked the dedifferentiation of biliary epithelial cells to hepatoblastlike cells via reduced Prox1 and Hnf4a induction [54]. In addition, mTORC1 and the BMP pathway were found to regulate the conversion of biliary epithelial cells to hepatocytes in zebrafish [55,56]. Inhibition of the mTORC1 signaling pathway abolished the conversion from biliary epithelial cells to hepatoblast-like cells via decreased Urb2-mediated protein synthesis [56], whereas the BMP pathway controlled the conversion of biliary epithelial cells through Tbx2b expression [55].…”
Section: Mechanism Of Biliary Epithelial Cell Plasticitymentioning
confidence: 99%
“…Using this model, we recently reported that BMP signaling regulates LPC-driven liver regeneration through Tbx2a and Id2a 75 and that bromodomain and extraterminal proteins (BET), Hdac1, Kdm1a, Sox9b, and Notch3 regulate LPC-driven liver regeneration 76,113,114 . Using the same zebrafish model, two other groups also reported that mTORC1 signaling regulates LPC-driven liver regeneration 115,116 .…”
Section: Animal Models For Lpc Researchmentioning
confidence: 92%
“…After extreme liver damage, regeneration is achieved via cholangiocytes transdifferentiation rather than self-replication, in zebrafish [174,175] and mice [176,177] (Figure 3E). The mTOR signaling pathway mediates liver regeneration after PH and initiates the transdifferentiation of biliary epithelial cells (BECs) after extreme liver injury [178,179].…”
Section: Roles Of Mtor In Liver Regenerationmentioning
confidence: 99%
“…Contributions of non-parenchymal cells (NPCs) can also be important for liver regeneration [174,176,177,179,200]. Expansion of BECs during ductular reaction (DR) is promoted by mTORC1 signaling after extreme liver injury in zebrafish and mice [179,200] (Figure 3E).…”
Section: Roles Of Mtor In Liver Regenerationmentioning
confidence: 99%